Electrochemical and AFM Characterization of G-Quadruplex Electrochemical Biosensors and Applications - Ana-Maria Chiorcea-Paquim; Ramon Eritja; Ana Maria Oliveira-Brett (Journal of Nucleic Acids, 2018)
Guanine-rich DNA sequences are able to form G-quadruplexes, being involved in important biological processes and representing smart self-assembling nanomaterials that are increasingly used in DNA nanotechnology and biosensor technology. G-quadruplex electrochemical biosensors have received particular attention, since the electrochemical response is particularly sensitive to the DNA structural changes from single-stranded, double-stranded, or hairpin into a G-quadruplex configuration. Furthermore, the development of an increased number of G-quadruplex aptamers that combine the G-quadruplex stiffness and self-assembling versatility with the aptamer high specificity of binding to a variety of molecular targets allowed the construction of biosensors with increased selectivity and sensitivity. This review discusses the recent advances on the electrochemical characterization, design, and applications of G-quadruplex electrochemical biosensors in the evaluation of metal ions, G-quadruplex ligands, and other small organic molecules, proteins, and cells. The electrochemical and atomic force microscopy characterization of G-quadruplexes is presented. The incubation time and cations concentration dependence in controlling the G-quadruplex folding, stability, and nanostructures formation at carbon electrodes are discussed. Different G-quadruplex electrochemical biosensors design strategies, based on the DNA folding into a G-quadruplex, the use of G-quadruplex aptamers, or the use of hemin/G-quadruplex DNAzymes, are revisited.